Metoda Koepckego-Papkowicza w Zastosowaniu Do Płyt Ortotropowych - K. Borsuk (Engineering Transactions, 1958)
The solution obtained by Koepcke and Papkovitch for isotropic plates clamped along two opposite edges can easily be generalized to analogous orthotropic plates. Depending on the value 02 of the Eq. (1.6), transcedental equations are obtained. The numerical values of the roots rk and tk are given for 0 = 1,1 and = 2,0.